2013
DOI: 10.1097/iae.0b013e318263d139
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Repeated Anti–vascular Endothelial Growth Factor Therapy in Eyes With Retinal Pigment Epithelial Tears

Abstract: Long-term visual results with repeated anti-VEGF therapy are not as devastating as suggested previously. Visual acuity and metamorphopsia improve with time as long as the neovascular membrane is inactive. Optical coherence tomography changes in the macular area reflect the visual acuity improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Moreover, it has been demonstrated that the precipitates in the su bretinal outer segment layer acted as hyperreflective spots in OCT ophthalmoscopy of central serous retinopathy (18,19) . Previous studies have reported repopulation and reattachment of RPE cells after tear formation, but these studies did not demonstrate healing of the hypoautofluorescence in the tear region (2,8) . Pece et al used OCT to show that reattachment of the margins of an RPE tear were healed by tissue remodeling and described how the disease can recur (20) .…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Moreover, it has been demonstrated that the precipitates in the su bretinal outer segment layer acted as hyperreflective spots in OCT ophthalmoscopy of central serous retinopathy (18,19) . Previous studies have reported repopulation and reattachment of RPE cells after tear formation, but these studies did not demonstrate healing of the hypoautofluorescence in the tear region (2,8) . Pece et al used OCT to show that reattachment of the margins of an RPE tear were healed by tissue remodeling and described how the disease can recur (20) .…”
Section: Discussionmentioning
confidence: 80%
“…After RPE tear formation, the PED usually becomes flat spontaneously. Reattachment of the free RPE edges to the Bruch membrane at a different location has recently been reported (2) . There is a possibility of improvement in patients with lower grade RPE tears (12) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations